Low‐frequency rTMS of the unaffected hemisphere in stroke patients: A systematic review. (2nd May 2017) - Sebastianelli, L.; Versace, V.; Martignago, S.; Brigo, F.; Trinka, E.; Saltuari, L.; Nardone, R.
Abstract : The aim of this review was to summarize the evidence for the effectiveness of low‐frequency (LF) repetitive transcranial magnetic stimulation (rTMS) over the unaffected hemisphere in promoting functional recovery after stroke. We performed a systematic search of the studies using LF‐rTMS over the contralesional hemisphere in stroke patients and reviewed the 67 identified articles. The studies have been gathered together according to the time interval that had elapsed between the stroke onset and the beginning of the rTMS treatment. Inhibitory rTMS of the contralesional hemisphere can induce beneficial effects on stroke patients with motor impairment, spasticity, aphasia, hemispatial neglect and dysphagia, but the therapeutic clinical significance is unclear. We observed considerable heterogeneity across studies in the stimulation protocols. The use of different patient populations, regardless of lesion site and stroke aetiology, different stimulation parameters and outcome measures means that the studies are not readily comparable, and estimating real effectiveness or reproducibility is very difficult. It seems that careful experimental design is needed and it should consider patient selection aspects, rTMS parameters and clinical assessment tools. Consecutive sessions of rTMS, as well as the combination with conventional rehabilitation therapy, may increase the magnitude and duration of the beneficial effects. In an increasing number of studies, the patients have been enrolled early after stroke. The prolonged follow‐up in these patients suggests that the effects of contralesional LF‐rTMS can be long‐lasting. However, physiological evidence indicating increased synaptic plasticity, and thus, a more favourable outcome, in the early enrolled patients, is still lacking. Carefully designed clinical trials designed are required to address this question. LF rTMS over unaffected hemisphere may have therapeutic utility, but the evidence is still preliminary and the findings need to be confirmed in further randomized controlled trials.